Incidence and risk factors of gestational diabetes mellitus in Goba town, Southeast Ethiopia: a prospective cohort study. Issue 9 (26th September 2022) - Atlaw, Daniel; Sahiledengle, Biniyam; Assefa, Tesfaye; Negash, Wogene; Tahir, Anwar; Regasa, Tadele; Tekalegn, Yohannes; Mamo, Ayele; Enegeda, Zinash Teferu; Solomon, Damtew; Gezahegn, Habtamu; Bekele, Kebebe; et al.
Abstract : Objective: Gestational diabetes mellitus (GDM) is becoming a public health concern in low/middle-income countries, and is known to cause severe morbidity and mortality for mothers and newborns. However, evidence reported for the incidence and risk factors of GDM is scant in Ethiopia. We aimed to assess the incidence of, and risk factors for, GDM in Goba town, Southeast Ethiopia. Design: Prospective cohort study. Setting: Goba town, Southeast Ethiopia. Participants: Four hundred eighty pregnant women on antenatal care follow-up from 30 April to 30 September 2021. Primary and secondary outcomes: Incidence and risk factors of GDM using fasting capillary blood glucose. Log-binomial model was used to identify the risk factors of GDM. Adjusted relative risk (aRR), along with 95% CIs, were calculated to estimate the strength of associations. Results: The cumulative incidence rate of GDM in this study was 15.7% (95% CI: 12.3% to 19.2%). Being unemployed (aRR=2.73; 95% CI: 1.36 to 5.47), having a family history of diabetes mellitus (DM) (3.01; 2.09 to 4.35), low physical activity (2.43; 1.11 to 5.32), inadequate dietary diversity (1.48; 1.29 to 1.92), anaemia (2.51; 1.32 to 3.54) and antenatal depression (4.95; 3.35 to 7.31) were significantly associated with GDM. Conclusion: The cumulative incidence of GDM was relatively high among the study participants. Having antenatal depression symptoms, low physical activity, inadequate dietary diversity, being unemployed, anaemia and a family history of DM were significant risk factors for GDM.